2020
DOI: 10.1364/boe.386228
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning segmentation for optical coherence tomography measurements of the lower tear meniscus

Abstract: The tear meniscus contains most of the tear fluid and therefore is a good indicator for the state of the tear film. Previously, we used a custom-built optical coherence tomography (OCT) system to study the lower tear meniscus by automatically segmenting the image data with a thresholding-based segmentation algorithm (TBSA). In this report, we investigate whether the results of this image segmentation algorithm are suitable to train a neural network in order to obtain similar or better segmentation results with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…For image segmentation, the support for a segmented area can be calculated as the number of pixels in the segmented area divided by the number of background pixels [40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For image segmentation, the support for a segmented area can be calculated as the number of pixels in the segmented area divided by the number of background pixels [40].…”
Section: Discussionmentioning
confidence: 99%
“…The two studies [78,40] showed that CNNs could be an appropriate tool for image analysis. CNNs are likely to increase in popularity within the field of DED due to promising results for solving image related tasks, including feature extraction.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
See 2 more Smart Citations
“…In dry eye disease, deep learning can be applied for the automatic segmentation of the anterior segment OCT image with a thresholding-based segmentation algorithm for the evaluation of the tear meniscus [ 91 ].…”
Section: Artificial Intelligencementioning
confidence: 99%